The accretion history of high-mass stars: an ArTéMiS pilot study of infrared dark clouds. Issue 3 (16th June 2020) - Peretto, N; Rigby, A; André, Ph; Könyves, V; Fuller, G; Zavagno, A; Schuller, F; Arzoumanian, D; Bontemps, S; Csengeri, T; Didelon, P; Duarte-Cabral, A; et al.
ABSTRACT: The mass growth of protostars is a central element to the determination of fundamental stellar population properties such as the initial mass function. Constraining the accretion history of individual protostars is therefore an important aspect of star formation research. The goal of the study presented here is to determine whether high-mass (proto)stars gain their mass from a compact (<0.1 pc) fixed-mass reservoir of gas, often referred to as dense cores, in which they are embedded, or whether the mass growth of high-mass stars is governed by the dynamical evolution of the parsec-scale clump that typically surrounds them. To achieve this goal, we performed a 350- μ m continuum mapping of 11 infrared dark clouds, along side some of their neighbouring clumps, with the ArTéMiS camera on APEX. By identifying about 200 compact ArTéMiS sources, and matching them with Herschel Hi-GAL 70 - μ m sources, we have been able to produce mass versus temperature diagrams. We compare the nature (i.e. starless or protostellar) and location of the ArTéMiS sources in these diagrams with modelled evolutionary tracks of both core-fed and clump-fed accretion scenarios. We argue that the latter provide a better agreement with the observed distribution of high-mass star-forming cores. However, a robust and definitive conclusion on the question of the accretion history of high-mass stars requires larger number statistics.